PENGARUH TERAPI BEKAM TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI KLINIK SEHAT MUGI BAROKAH KARAKAN GODEAN SLEMAN YOGYAKARTA - Winda Astuti; Nur Yeti Syarifah (STIKES Wira Husada Yogyakarta, 2018)
Background: Hypertension is a degenerative disease that becomes a serious problem but one way to reduce hypertension by means of cupping therapy.Objective: To know the effect of bruise therapy on blood pressure in hypertensive patients in healthy clinic Mugi Barokah Karakan, Godean, Sleman, Yogyakarta Method: This research is a quantitative research, using quasi experimental (quasi experiment) with pre and posttest without control. The population of this study were hypertensive patients who performed bruise therapy with population taking at the clinic of bruise therapy as much as 15 respondents. The sampling technique used incidental samples, with a sample size of 15 people. Data collection tool using check list.Results: The results showed the value of bivariate analysis with the wilxocon test formula that there was an effect of bruise therapy on blood pressure in hypertensive patients after bruise. That there was an average decrease in blood pressure on 15 respondents of hypertension before and after cupping therapy showed with p = 0,000 and p = 0.003 where p <0.005 Conclusion: There is inﬂ uence of bruise therapy to blood pressure in hypertension patient at Healthy Clinic Mugi Barokah Karakan Godean Sleman Yogyakarta